The effects of human resource practices on firm performance in Thailand's manufacturing industry - Tangthong, Sorasak; Trimetsoontorn, Jirasek; Rojniruttikul, Nuttawut (My University, 2015)
The purpose of this study is to determine the effects of human resource management (HRM) practices on firm performance in Thailand's manufacturing industrial Zone 2, a region that has seen an influx of foreign investment. Twenty-three theoretically based hypotheses have been developed that point to possible positive and negative relationships between HRM practices, mediating variables and firm performance. A total of 224 top managers, business leaders and line managers provided the input that was examined and then empirically tested using analysis of moment structures (AMOS) Path Analysis. The results show that HRM practices do strongly influence firm performance, a conclusion that is not only consistent with the results of previous research on the subject, but also indicative of methods that of ever-increasing importance to long-term growth in organisations. This study has provided new insight into HRM practices and firm performance, getting to the heart of the role that mediating variables play in the network of relationships.
Keywords: Firm performance; Globalisation; HRM; Human resource management; Human resource practices; Thailand's manufacturing industry